Propyl (E)-3-(furan-2-yl) Acrylate: a synthetic antifungal potential with a regulatory effect on the biosynthesis of ergosterol in Candida Albicans - Paulo César Trindade da Costa; Thales Luciano Bezerra Santos; Jaqueline Ferreira Ramos; Jonh Anderson Macêdo Santos; Francinalva Dantas de Medeiros; Juliano Carlo Rufino de Freitas; Wylly Araújo de Oliveira (Universidade de São Paulo, 2023)
Abstract The genus Candida represents the main cause of infections of fungal origin. Some species stand out as disease promoters in humans, such as C. albicans, C. glabrata, C. parapsilosis, and C. tropicalis. This study evaluated the antifungal effects of propyl (E)-3-(furan-2-yl) acrylate. The minimum inhibitory concentration of the synthetic compound, amphotericin B and fluconazole alone against four species of Candida ranged from 64 to 512 μg/mL, 1 to 2 μg/mL, and 32 to 256 μg/mL, respectively. The synergistic effect of the test substance was observed when associated with fluconazole against C. glabrata, there was no antagonism between the substances against any of the tested strains. The potential drug promoted morphological changes in C. albicans, decreasing the amount of resistance, virulence, and reproduction structures, such as the formation of pseudohyphae, blastoconidia, and chlamydospores, ensuring the antifungal potential of this substance. It was also possible to identify the fungicidal profile of the test substance through the study of the growth kinetics of C. albicans. Finally, it was observed that the test compound inhibited the ergosterol biosynthesis by yeast.